Communication of mechanically ventilated patients in intensive care units - Martinho, Carina; Tello Rodrigues, Inês (My University, 2016)
Objective: The aim of this study was to translate and culturally and linguistically adapt the Ease of Communication Scale and to assess the level of communication difficulties for patients undergoing mechanical ventilation with orotracheal intubation, relating these difficulties to clinical and sociodemographic variables. Methods: This study had three stages: (1) cultural and linguistic adaptation of the Ease of Communication Scale; (2) preliminary assessment of its psychometric properties; and (3) observational, descriptive-correlational and cross-sectional study, conducted from March to August 2015, based on the Ease of Communication Scale - after extubation answers and clinical and sociodemographic variables of 31 adult patients who were extubated, clinically stable and admitted to five Portuguese intensive care units. Results: Expert analysis showed high agreement on content (100%) and relevance (75%). The pretest scores showed a high acceptability regarding the completion of the instrument and its usefulness. The Ease of Communication Scale showed excellent internal consistency (0.951 Cronbach’s alpha). The factor analysis explained approximately 81% of the total variance with two scale components. On average, the patients considered the communication experiences during intubation to be “quite hard” (2.99). No significant correlation was observed between the communication difficulties reported and the studied sociodemographic and clinical variables, except for the clinical variable “number of hours after extubation” (p < 0.05). Conclusion: This study translated and adapted the first assessment instrument of communication difficulties for mechanically ventilated patients in intensive care units into European Portuguese. The preliminary scale validation suggested high reliability. Patients undergoing mechanical ventilation reported that communication during intubation was “quite hard”, and these communication difficulties apparently existed regardless of the presence of other clinical and/or sociodemographic variables.
A comunicação dos doentes mecanicamente ventilados em unidades de cuidados intensivos
Keywords: Communication; Nonverbal communication; Communication barriers; Speech-language pathology; Mechanical ventilation; Intensive care units